An inconsistency in using stock flow consistency in modelling the monetary profit paradox - Marcel R. de la Fonteijne (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
In order to understand the sources of profits or monetary profits of capitalists and firms, the author examines the phrase of Marx: 'Die Gesamtklasse der Kapitalisten kann nichts aus der Zirkulation herausziehen, was nicht vorher hineingeworfen war.' (The class of capitalists cannot extract from the circulation what has not previously been thrown in.) Steve Keen studied the monetary paradox and contrary to circuitists he came to the conclusion that capitalists can make a monetary profit with the possibility to earn enough to repay their debt, with positive balances for all actors. The author demonstrates that Keen made a fundamental mistake and is using the Stock Flow Consistency Principle in an inconsistent way by combining it with behavioral equations in a dynamic model. The solution presented here shows not only problems with the numbers but with the method. This solution resolves a dispute between Keen and circuitists and implies that, in a Wicksellian pure credit economy, it remains impossible for all actors to gain a monetary profit.
Keywords: C50; C60; E11; E12; E20; E25; E44; G00; 330; Monetary profit paradox; stock flow consistency; circuit theory; endogenous money; Wicksellian pure credit economy